2017
DOI: 10.15421/021770
|View full text |Cite
|
Sign up to set email alerts
|

Radio monitoring of plant products and soils of Polesia, Zhytomyr region, during the long-term period after the disaster at the Chornobyl Nuclear Power Plant

Abstract: The article highlights the consequences of the Chernobyl disaster. Northern Polesia has been and still remains the most polluted area. Full scale and limited economic activity is carried out on part of the contaminated territories. The zone of radioactive contamination includes half of the territory of this region, one third of the agricultural land and almost the same amount of the arable land. 9 districts, 734 towns and villages are located within the zone of radioactive contamination. In the long-term perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…They are adapted to life in a variety of habitats and produce biomass containing a wide variety of compounds that can be used in the food, pharmaceutical, and cosmetic industries, and for the production of biofuels, etc. [3][4][5][6]. Of significant interest to the food and feed industry is the ability of microalgae to produce carotenoids such as β-carotene, astaxanthin, lutein, as well as lipids containing a wide variety of fatty acids, including long-chain polyunsaturated fatty acids (PUFAs) from the omega-3 and omega-6 [7][8][9][10][11][12][13] group.…”
Section: Introductionmentioning
confidence: 99%
“…They are adapted to life in a variety of habitats and produce biomass containing a wide variety of compounds that can be used in the food, pharmaceutical, and cosmetic industries, and for the production of biofuels, etc. [3][4][5][6]. Of significant interest to the food and feed industry is the ability of microalgae to produce carotenoids such as β-carotene, astaxanthin, lutein, as well as lipids containing a wide variety of fatty acids, including long-chain polyunsaturated fatty acids (PUFAs) from the omega-3 and omega-6 [7][8][9][10][11][12][13] group.…”
Section: Introductionmentioning
confidence: 99%
“…Later this peculiarity attracted the biochemists' attention and it was found that C. oleofaciens is characterized by accumulation of a large amount of fatty acids: unsaturated -oleic and linoleic ones, saturated -palmitic one (Cojocaru et al, 1988). Hereafter, with the development of ideas for the production of biomass fuel, it was found that saturated fatty acids increase the octane number and biofuel resistance to degradation, unsaturated fatty acids reduce the pour point and gelation of fuel at low temperatures, and algae are generally a promising raw material for biodiesel production (Talebi et al, 2013;Maltsev et al, 2017b). These discoveries led to a further study of the biochemistry of C. oleofaciens.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuating asymmetry index was used to test the levels of radionuclide contamination after the Chornobyl disaster [18]. For this area, high informativity and sensitivity of the species Potamogeton natans L. were noted [19].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%